A new species of Hymenodora (Crustacea: Decapoda: Oplophoridae) from abyssopelagic depths of the central North Pacific Ocean - Wasmer, Robert A. (Zootaxa, 2022)
Hymenodora chacei n. sp. collected from abyssopelagic waters of the central North Pacific Ocean is described. The new species differs from the four previously known species of the genus by having eyes with corneas reduced, with few or no facets, and lacking pigmentation. The ocular peduncles are broad and short, with prominent pointed terminal tubercles overreaching the corneas. The gastric region of the carapace has a corrugated appearance. Only one specimen has a relatively undamaged telson, which somewhat resembles that of Hymenodora acanthitelsonis. A key to the known species of Hymenodora is provided. Two specimens of the genus which cannot be determined as to species are also reported. Recent studies of the molecular phylogeny of the oplophorid shrimps are briefly discussed.